Brazil - Financing Municipal Investment : Issues and Options - World Bank (Washington, DC, 2013)
This report explores alternative ways to finance municipal capital expenditures while maintaining macroeconomic stability and fiscal discipline. It tries to estimate the financing effort that municipalities will need to make in order to meet the demand for infrastructure services over the next five to 10 years, taking into account the municipalities' expected resources from local taxes, user charges, and intergovernmental transfers. The report is organized into six chapters. The introduction describes the overall problem, main issues, methodology, and analytical framework. Chapter 2 explains the context under which municipalities operate, and it identifies the main financial trends in the sector. Chapter 3 discusses how to increase municipal current savings to enable municipal governments to finance investment and leverage borrowing. Chapter 4 focuses how to ensure that the existing municipal credit systems operate efficiently, that municipalities with "good" projects find adequate long-term financing, and that credit is allocated more by market rules and less by political factors. Chapters 5 and 6 discusses how to support the involvement of the private sector in the financing of municipal infrastructure and in helping the transition toward less regulated credit systems.